Management Regimes and Institutional Arrangement in FloodplainWetlands Fisheries of Assam: An Evaluation (Indian Journal of Extension Education, 2011)
Assam is endowed with copious aquatic wealth in the form of beels, swamps, ponds and rivers. The floodplain wetlands (beels) extending over one lakh hectare, constitute the most important fishery resource of the state. The floodplain wetlands are used as multiple use and multiple user system. These wetlands are the common property resource and under different management regimes. Multiple institutions play its role through ownership and control over the fisheries of wetlands. A large number of stakeholders are associated directly and indirectly with the beel, these include fishers, lessees, various state government departments, AFDC, financial institutions, research institutes, NGO’s etc. These wetlands are under various management regimes, i.e., private management (individuals and groups), fishermen cooperative management, Community-based fisheries management (decentralized management, Government works as facilitator) and open access. An attempt has been made through this communication to describe management regimes and institutional arrangement in the frame work of stakeholders’ mechanism of access to utilize the floodplain wetland resources for outcomes (positive or negative).